Separation, Characterization and Discriminant Analysis of Subvisible Particles in Biologics Formulations - Akhunzada, Zahir S.; Hubert, Mario; Sahin, Erinc; Pratt, James (Current Pharmaceutical Biotechnology, 2019)
Background: The presence of subvisible particles (SVPs) in parenteral formulations of biologics is a major challenge in the development of therapeutic protein formulations. Distinction between proteinaceous and non-proteinaceous SVPs is vital in monitoring formulation stability. Methods: The current compendial method based on light obscuration (LO) has limitations in the analysis of translucent/low refractive index particles. A number of attempts have been made to develop an unambiguous method to characterize SVPs, albeit with limited success. Results: Herein, we describe a robust method that characterizes and distinguishes both potentially proteinaceous and non-proteinaceous SVPs in protein formulations using Microflow imaging (MFI) in conjunction with the MVAS software (MFI View Analysis Suite), developed by ProteinSimple. The method utilizes two Intensity parameters and a morphological filter that successfully distinguishes proteinaceous SVPs from non-proteinaceous SVPs and mixed aggregates. Conclusion: The MFI generated raw data of a protein sample is processed through Lumetics LINK software that applies an in-house developed filter to separate proteinaceous from the rest of the particulates.
Keywords: non-proteinaceous particles